Sustainable materials selection based on flood damage assessment for a building using LCA and LCC. (10th June 2019) - Balasbaneh, Ali Tighnavard; Bin Marsono, Abdul Kadir; Gohari, Adel
Abstract: Flood risk is increasing rapidly around the world owing to the influence of climate change on precipitation levels. The refurbishment process is a complicated method of building construction after flooding. This study assesses all building costs in parallel with environmental emissions after repairs in a flood zone, in non-flood situations and when a flood hits the building, to determine the feasibility of repairs. Five types of building materials including common brick, concrete block, steel wall panels, wood, and precast concrete framing were assessed with a full life cycle assessment (LCA) and life cycle cost (LCC) assessment under non-flood, low-flood, and high-flood conditions. The result of greenhouse gas analysis showed that timber was the best choice for constructing the building, while, in case of flood occurrence, precast concrete framing shows better performance by releasing less CO2 after the repair stage. The result of cost analysis indicated that despite timber being an ideal material for use in building construction, it is the costliest option in a high-flood situation due to its high repair costs. The benchmark results show that timber and steel frame were the worst materials to use in a flood zone, while brick was the most sustainable one. The findings of this paper prove that wood as a building material in flood zones is not ideal and that alternative materials such as brick have better functionality in terms of both global warming mitigation and LCC. The findings of this study provide insight into enhancing coordination among government bodies in the provision of post-disaster permanent housing adapted to climate change. Highlights: We introduce skeleton damage from flooding into residential buildings. Calculate life cycle costs and life cycle carbon in damage after flooding. Finding shows that wood is the best material for Non-flood zone areas. The total embodied carbon emission of wood building is higher than concrete after maintenance from flood occurrence. The cost of wood structure after flood will be even higher than concrete and brick building.